Effect of the Type of Intraoperative Restrictive Fluid Management on the Outcome of Pancreaticoduodenectomy: A Systematic Review and Meta-Analysis - Jian Wang; Wenchong Sun; Zhongbao Fan; Xin An; Ling Pei (Gastroenterology Research and Practice)
Background. The perioperative management of pancreaticoduodenectomy is complicated, and the significant morbidity and mortality may be influenced by the method of intraoperative fluid management. Whether intraoperative restrictive fluid therapy can affect the outcomes of pancreaticoduodenectomy or not is controversial. Methods. PubMed, EMBASE, Cochrane Library, and clinicaltrials.gov were searched for prospective and retrospective studies comparing restrictive and liberal intraoperative fluids in patients undergoing pancreaticoduodenectomy. Following study identification, a systematic review and meta-analysis were performed. Results. Fourteen studies, including six prospective trials and eight retrospective studies, involving 2,596 patients, were included. Intraoperative restrictive fluid regimens had no effect on the mortality compared to liberal fluid regimens in the overall cohort (odds ratio [OR]: 1.39; 95% confidence interval [CI]: 0.82–2.35, p=0.773). Liberal fluid regimens could increase the risk of pulmonary adverse events (OR: 1.66; 95% CI: 1.10–2.50, p=0.131) and prolong the length of hospital stay (SMD -0.10; 95% CI -0.19– -0.01, p=0.375). There were no significant differences in the incidence of pancreatic fistulas. Conclusions. Restrictive fluid regimens have a slight effect on the outcomes of pancreaticoduodenectomy. The clinical relevance of this finding needs to be interpreted. The existing evidence may not be adequate; therefore, further studies are warranted.